Liquefiable Ground Treatment Using Cruciform Section Probe Resonant Compaction Method: A Case Study in the Xitong Expressway, Eastern China - Guangyin Du; Han Xia; Jun Cai; Huangsong Pan; Changshen Sun (Advances in Civil Engineering)
The foundation treatment of liquefiable soil has always been an important part of construction. Sand liquefaction decreases the foundation capacity and can cause severe building, highway, or bridge engineering accidents. This study used self-developed cruciform section probe resonant compaction equipment (CSPRCE) to evaluate the applicability and reinforcement effect of the Xitong Expressway foundation. The cone penetration test (CPT) results showed that this soil was liquefiable ground requiring treatment before construction. Laboratory tests illustrated that the clay particle content was nearly 10% in the surface layer, indicating that the traditional resonant compaction probe (RCP) would not provide effective reinforcement; therefore, we adopted the new resonant compaction method (RCM) for the reinforcement process. The CPT and standard penetration test (SPT) results after foundation reinforcement indicated that the cruciform section probe resonant compaction method (CSPRCM) is suitable for treating the Xitong Expressway liquefiable foundation. Before reinforcement, 7-8 liquefiable soil layers were observed, whereas after reinforcement, no foundation testing points were liquefiable. Cone resistance and unit sleeve friction resistance were both improved by a factor of nearly 3 after the CSPRCM reinforcement. The CSPRCM has wider applicability than traditional vibrating compaction methods, especially for sites with a high content of silt and clay particles. The strengthening mechanism of the CSPRCM is a vibration hammer that generates vibrational energy to obliterate the original soil structure and render the sand completely liquefied; the soil particles then rearrange to form a new structure.